Buddhist Responses to Globalisation, edited by Leah Kalmanson and James Mark Shields - Dixon, Graham (Buddhist Studies Review, 2015)
Buddhist Responses to Globalisation, edited by Leah Kalmanson and James Mark Shields, Lexington Books, 2013. xiv+182pp. $80.00. ISBN-13: 9780739180549.